ANALISIS TOTAL QUALITY MANAGEMENT (TQM) PADA PENDIRIAN TK ISLAM TERPADU MUTIARA PLUS BANGUNTAPAN - Muhammad Abdul Latif; Erni Munastiwi; Deska Puspita; Adinda Putri Amanah (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
The advance of times is the biggest challenge of educational institutions, especially in Early Childhood Education Institutions which must strive in totality to become quality institutions. The emergence of inadequate PAUD institutions or accreditation that has not yet reached PAUD institution accreditation standards is a problem in this study. The purpose of the study was to examine the management analysis of the establishment of PAUD institutions with a Total Quality Management (TQM) approach at TK IT Mutiara Plus Banguntapan, Bantul. This research method uses qualitative research with a case study approach. Data collection techniques with observation, interviews, and documentation. The analysis used the Milles and Huberman model. The results of this study found that the Management of PAUD Institution in TK IT Mutiara Plus Banguntapan, Bantul was well organized. After being analyzed by TQM there are no principles or references that are not applied. This is evidenced by the advancement in the quality of TK IT Mutiara Plus Banguntapan, Bantul institutions from the initial establishment until now.